Modifikasi Permainan Puzzle Sebagai Media Pembelajaran Ekonomi Berbasis Make A Match Kelas XI Untuk Meningkatkan Hasil Belajar - Ariyawan, Vivi Feby (Universitas Pendidikan Ganesha, 2021)
Research is in the background because there is no learning media in schools to help the teaching and learning process in economic subjects. Often found low learning motivation in students. In the classroom there is no learning media that supports and increases student learning outcomes in economic subjects in particular, so this study develops a make a match based puzzle game learning media which aims to determine the feasibility, effectiveness, practicality of learning media on student learning outcomes. This research is a development research with Four-D models which only reaches the Develop stage. The trial design of this study used a pretest-posttest group design. The test subjects in this study were 24 students of SMA Negeri 3 Bojonegoro, class XI IPS 1. The results of this study met the feasible requirements, obtained a very feasible category of 91% in media validation, obtained a very feasible category of 100% in material validation, obtained a feasible category of 80% in the evaluation evaluation, obtained a very feasible category of 100% on the validation of effectiveness, and obtained a very feasible category of 100% in practicality, obtained a very feasible category of 95.07% in the response of students. From the research results it can be concluded that the learning media based on make a match puzzle games developed are feasible, effective and practical to use.